If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 115 + -3x = 6x + 16 Reorder the terms: 115 + -3x = 16 + 6x Solving 115 + -3x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 115 + -3x + -6x = 16 + 6x + -6x Combine like terms: -3x + -6x = -9x 115 + -9x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 115 + -9x = 16 + 0 115 + -9x = 16 Add '-115' to each side of the equation. 115 + -115 + -9x = 16 + -115 Combine like terms: 115 + -115 = 0 0 + -9x = 16 + -115 -9x = 16 + -115 Combine like terms: 16 + -115 = -99 -9x = -99 Divide each side by '-9'. x = 11 Simplifying x = 11
| 4p+3=6p-15 | | a+19=28 | | 4(w-2)=-8 | | 7c+2c+3c-2= | | 14.31+w=70 | | 9+3=6-7+12 | | -7y-10=2y+8 | | 3(x-7)+x=19 | | -5x-7=23 | | 19=-3x+34 | | 11=10+y | | -5x+11=11 | | -2y-9=3y+21 | | 2(x+7.3)=6x-0.83 | | 28.08+8=f | | 2r-24=-2(r-2) | | 43=r+7.3 | | 7+3v=-7+5v | | Y=x^2+2x-120 | | 3x^4y^3-3y^3= | | 180=90+x+x-10 | | 9(x-4)+13=4x+23 | | Y^2-20=8y | | 61-4x=23x+16 | | 3x-4x+2=x-8 | | 7x+4=4x-3 | | -29-(-6)= | | N+3=-5+6n-n | | -5(2p+4)-38=2(3p+3) | | -3=4y-10 | | -1-(-45)= | | -5-6p=1-8p |